Non-randomized safety and performance evaluation of the av-Guardian vascular access system. Issue 5 (September 2020) - Tan, Chieh Suai; Tan, Seck Guan; Wong, Chi Leung Julian; Wee, Bernard; Wong, Weng Kin; Choke, Edward Tieng Chek; Tan, Ru Yu; Liu, Peiyun; Homer-Vanniasinkam, Shervanthi; Lau, Titus; Choong, Lina Hui Lin
Introduction: The ability to successfully cannulate the arteriovenous fistula reliably is a critical step in the delivery of hemodialysis therapy. The av-Guardian vascular access system (Advent Access, Singapore) is designed to overcome the technical barrier to establishing reliable blunt needle access in patients with mature arteriovenous fistula. Methods: This was a first-in-man, prospective, non-randomized trial (registered on the Australian New Zealand Clinical Trial Registry (ACTRN12617000501347)) performed to assess the safety and feasibility of achieving repeatable successful cannulation via av-Guardian vascular access system to facilitate blunt needling in patients with mature arteriovenous fistula. The primary endpoints of the study included rate of successful hemodialysis sessions via av-Guardian vascular access system cannulation over 3 months and safety of the implants. Results: A total of six patients (four patients with brachiocephalic and two with radiocephalic arteriovenous fistula) were enrolled in the study. A pair of av-Guardian vascular access system were implanted, one each at the arterial and venous cannulation sites, under local anesthesia. Overall, the rate of successful cannulation through the av-Guardian vascular access system over 3 months in 216 hemodialysis sessions was 98.1% (212/216) at the arterial site and 94.4% (204/216) at the venous site. Significantly, 90% and 85.5% of the cannulations at the arterial and venous site, respectively, were successful at first attempt. Blood flow rates within the arteriovenous fistula were unaffected by the devices. Conclusion: The results demonstrated the safety and feasibility of a subcutaneously implanted, extravascular device in achieving repeatable successful cannulation via a constant site, to facilitate blunt needling in matured arteriovenous fistula in limited number of patients.